Continuous Production of Biodiesel from Rubber Seed Oil Using a Packed Bed Reactor with BaCl2 Impregnated CaO as Catalyst - Achanai Buasri; Vorrada Loryuenyong (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The goal of this research was to test barium chloride (BaCl2) impregnated calcined razor clam shell as a solid catalyst for transesterification of rubber seed oil (RSO) in a packed bed reactor (PBR). The waste razor clam shells were crushed, ground, and calcined at 900 °C in a furnace for 2 h to derive calcium oxide (CaO) particles. Subsequently, the calcined shells were impregnated with BaCl2 by wet impregnation method and recalcined at 300 °C for 2 h. The synthesized catalyst was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), Brunauer-Emmett-Teller (BET) surface area, and basic strength measurements. The effects of various parameters such as residence time, reaction temperature, methanol/oil molar ratio, and catalyst bed length on the yield of fatty acid methyl ester (FAME) were determined. The BaCl2/CaO catalyst exhibited much higher catalytic activity and stability than CaO catalyst influenced by the basicity of the doped catalyst. The maximum fatty acid methyl ester yield was 98.7 % under optimum conditions (residence time 2.0 h, reaction temperature 60 °C, methanol/oil molar ratio 12:1, and catalyst bed length 200 mm). After 6 consecutive reactions without any treatment, fatty acid methyl ester yield reduced to 83.1 %. The option of using waste razor clam shell for the production of transesterification catalysts could have economic benefits to the aquaculture and food industries.